Fosfomycin: An Alternative Therapy for the Treatment of UTI Amidst Escalating Antimicrobial Resistance - Sabharwal, Ekadashi Rajni (J Clin Diagn Res, 2015)
INTRODUCTION: Urinary tract infections (UTIs) are the most commonly encountered infectious diseases. The current study was undertaken with a dual purpose, to provide an insight into the current scenario of the microorganisms causing UTI, their antimicrobial sensitivity patterns and also try and evaluate the activity of fosfomycin against E. coli, both ESBL producers as well as non-producers. MATERIALS AND METHODS: The study was conducted prospectively in the Department of Microbiology of a tertiary care hospital from January to June 2014. A total of 358 isolates from the urinary samples of the patients with a diagnosis of urinary tract infection were included in the study. Antibiotic sensitivity testing and extended spectrum beta lactamase (ESBL) production testing was done as per CLSI guidelines. RESULTS: These represented 297 (82.9%) gram-negative isolates and 61 (17%) gram-positive isolates. The 297 gram-negative isolates represented 265 (89.2%) members of the Enterobacteriaceae, 185 (69.8%) of which were Escherichia coli, 66 (24.9%) Klebsiella spp. and 14 (5.28%) Proteus spp. Non-fermentative Pseudomonas spp were isolated from 8.9% cases. Amongst the Gram negative isolates tested, 78 (21.8%) formed extended spectrum beta-lactamases. Of the total 358 isolates tested, 338 (94.4%) were found to be susceptible to fosfomycin. CONCLUSION: Fosfomycin showed good activity against both ESBL-producing and ESBL-negative E. coli isolates. The main finding of our study is that fosfomycin exhibits excellent antimicrobial activity even against the isolates with relatively high levels of antimicrobial resistance and hence can be a useful drug in our armamentarium.